Global Distribution and Projected Variations of Compound Drought‐Extreme Precipitation Events - Siqi Deng; Dongsheng Zhao; Ziwei Chen; Lei Liu; Yu Zhu; Ke Wang; Xuan Gao; Hanqian Wu; Du Zheng (Earth's Future)
Abstract The compound drought‐extreme precipitation event (CDEP) is one of the most impactful successive compound events that shift from drought to extreme precipitation in the same location within a short period. Due to its dual characteristics of drought and flood, CDEP tends to be more destructive than the impact of individual drought or flood. Yet few studies have analyzed the likelihood of CDEP at different time intervals and their potential variations under global warming. In this study, we assessed the coincidence rate between droughts and extreme precipitation events at 1‐month (CDEP‐1), 2‐month (CDEP‐2), and 3‐month (CDEP‐3) intervals, as well as their potential changes in a 1.5 and 2°C warming world (under both SSP2‐4.5 and SSP5‐8.5 scenarios). Our results suggest that global droughts and extreme precipitation events have coincided more frequently at 1‐month interval than at 2‐ and 3‐month intervals during the period 1985–2014. The global average coincidence rates of CDEP‐1, CDEP‐2, and CDEP‐3 are 24%, 10%, and 7%, respectively. Notably, the coincidence rate of CDEP‐1 exceeded 40% in Eastern Asia, north‐eastern North America, and India, indicating that more than 40% of droughts have been followed by extreme precipitation events in the next month after drought termination. Under both SSP2‐4.5 and SSP5‐8.5 scenarios, climate warming will increase the coincidence rate of CDEP‐1, CDEP‐2, and CDEP‐3, especially will lead to higher values in the coincidence rate of CDEP‐1. This study contributes to a better understanding of the patterns of CDEP and helps to develop more targeted risk management strategies.